Use of Blockchain for Data Security in E-Government Systems - Achmad Ridwan; Kailie Maharjan; Krim Ulwi (Yayasan Adra Karima Hubbi, 2024)
The increasing reliance on digital platforms for public administration has heightened concerns about data security in e-government systems. Cyber threats, unauthorized access, and data breaches pose significant risks to the integrity and confidentiality of sensitive governmental information. Blockchain technology, with its decentralized and tamper-proof nature, offers a promising solution for enhancing data security in e-government systems. This research explores the use of blockchain to safeguard data in e-government platforms, focusing on its potential benefits, challenges, and implementation strategies. The study adopts a mixed-method approach, combining a systematic literature review and expert interviews. The literature review analyzed 50 academic articles and industry reports, while interviews with 10 blockchain experts provided practical insights. Key factors such as data integrity, transparency, and access control were evaluated to determine blockchain’s effectiveness in addressing e-government security challenges. The findings reveal that blockchain significantly improves data security by ensuring immutability, enabling secure data sharing, and reducing reliance on central authorities. Experts highlighted blockchain’s potential to enhance transparency and accountability while maintaining privacy through cryptographic techniques. However, challenges such as high implementation costs, scalability issues, and regulatory uncertainties were identified as barriers to adoption. The study concludes that blockchain can revolutionize e-government data security by offering a robust and decentralized framework. Addressing the challenges of implementation and policy alignment will be critical for realizing its full potential. Future research should focus on pilot projects and sector-specific adaptations to accelerate blockchain adoption in e-government systems.